The fertility of the Irish in the United States in 1910 - Timothy W. Guinnane; Carolyn M. Moehling; Cormac Ó Gráda (University College Dublin, Department of Economics, 2004)
In most western societies, marital fertility began to decline in the nineteenth century. But in Ireland, fertility in marriage remained stubbornly high into the twentieth century. Explanations of this focus on the influence of the Roman Catholic Church in Irish society. These arguments are often backed up by claims that the Irish outside of Ireland behaved the same way. This paper investigates these claims by examining the marital fertility of Irish Americans in 1900 and 1910. We find that Irish fertility patterns did not survive the Atlantic crossing. The Irish in America had smaller families than couples in both rural and urban Ireland. But Irish immigrants still had large families relative to the native-born population in the U.S. This higher marital fertility of Irish immigrants cannot be attributed to differences in other population characteristics. Conditional on observable characteristics, Irish immigrants had larger families.
hdl:10197/478
Keywords: J13; N3; 330; Ireland; United States; Fertility; Fertility Transition; Immigration; Fruchtbarkeit; Einwanderung; Iren; USA